Replacing cottonseed meal and sorghum with dried distillers' grains with solubles enhances the growth performance, carcass traits, and meat quality of feedlot lambs. Issue 2 (13th April 2022) - Quadros, Danilo G; Whitney, Travis R; Kerth, Chris R
Abstract: We evaluated the impacts of substituting cottonseed meal (CSM) and sorghum grain (SG) with dried distillers` grains with solubles (DDGS) in lamb feedlot diets on the dry matter intake (DMI), the growth performance, blood serum analysis, feces phosphorus (P) and nitrogen (N), wool production and quality, carcass traits, adipose tissue fatty acid (FA) profiles, and sensory panel tests. For 72 d, Rambouillet wether lambs ( n = 44, initial body weight, BW = 28.8 ± 3.3 kg) were individually fed ad libitum pelleted diets containing DDGS that replaced 0% (0DDGS), 25% (25DDGS), 50% (50DDGS), or 75% (75DDGS) of the CSM and SG in a completely randomized design trial. Linear and quadratic effects of DDGS levels on the response variables were analyzed. Treatment × day interactions ( P < 0.001) were observed for BW and DMI. As the DDGS level was increased, DMI (from days 21 to 70), lamb BW (from days 56 to 70), average daily gain, blood urea nitrogen and P, and fecal P linearly increased ( P ≤ 0.05). Fecal N quadratically increased ( P = 0.01), but no effects were found for gain:feed, blood insulin-like growth factor-1, or calcium. No differences in wool production or most of the wool quality parameters were detected. Adipose tissue stearic acid linearly increased ( P = 0.02), linoleic acid quadratically increased ( P = 0.01), and oleic acid tended to quadratically decrease ( P = 0.08) as the DDGS increased in the diets. Increasing the DDGS level in the diets quadratically increased the hot carcass weight ( P = 0.02), backfat thickness ( P = 0.04), and body wall thickness ( P < 0.001) while having no impact on the longissimus muscle area. As the DDGS increased in the diet, juiciness, tenderness, and overall acceptability linearly increased ( P ≤ 0.05), while having no effect on the cook-loss, flavor intensity, or off-flavor detectability. Replacing 50% of CSM and SG with DDGS improved growth performance and enhanced the carcass and meat quality. Lay Summary: Dried distillers' grains with solubles (DDGS), mostly derived from corn ethanol production in the U.S., is an easily available feedstuff that can be used in animal rations to replace traditionally and frequently more expansive sources of energy and protein. In this study, we tested replacing up to 75% of sorghum grain and cottonseed meal with DDGS for finishing lambs in feedlot conditions. The DDGS in lamb diets increased intake, final body weight, and average daily gain while maintaining an unaltered gain:feed ratio, which may increase profitability if the DDGS price is competitive. Important carcass traits were improved by DDGS inclusion such as the hot carcass weight and backfat thickness; however, there was no effect on the longissimus muscle area. Although the fat percentage and most of the adipose tissue fatty acids (FA) in meat had no significant differences with increased DDGS, some major FA had remarkable alterations, such as increased stearic and linoleic acids and decreased oleic acid. Increasing the DDGS improved the meat juiciness, tenderness, and overall acceptability while having no impact on the cook-loss, flavor intensity, or off-flavor detectability. In conclusion, moderate levels of substitution (50%) led to overall better results and therefore are recommended. Abstract : This research will guide animal nutritionists to maximize the inclusion of DDGS in feedlot lamb diets to increase growth performance and enhance carcass traits and meat quality.